A continuous integration and web framework in support of the ATLAS publication process. (11th May 2021) - Araque Espinosa, J.P.; Baldi Levcovitz, G.; Bianchi, R.M.; Brock, I.; Carli, T.; Castro, N.F.; Ciocio, A.; Colautti, M.; Da Silva Menezes, A.C.; De Oliveira da Fonseca, G.; Domingues Macedo Alves, L.; Hoecker, A.; et al.
Abstract: The ATLAS collaboration defines methods, establishes procedures, and organises advisory groups to manage the publication processes of scientific papers, conference papers, and public notes. All stages are managed through web systems, computing programs, and tools that are designed and developed by the collaboration. A framework called FENCE is integrated into the CERN GitLab software repository, to automatically configure workspaces where each analysis can be documented by the analysis team and managed by the relevant coordinators. Continuous integration is used to guide the writers in applying consistent and correct formatting when preparing papers to be submitted to scientific journals. Additional software assures the correctness of other aspects of each paper, such as the lists of collaboration authors, funding agencies, and foundations. The framework and the workflow therein provide automatic and easy support to the researchers and facilitates each phase of the publication process, allowing authors to focus on the article contents. The framework and its integration with the most up to date and efficient tools has consequently provided a more professional and efficient automatized work environment to the whole collaboration.